Sensorineural hearing loss in patients with Kawasaki disease - Sun Young Park; Young Hyun Kim; Yeo Hyang Kim; Myung Chul Hyun; Young Hwan Lee (Korean Pediatric Society, 2015)
PurposeKawasaki disease involves acute febrile systemic vasculitis that can cause a variety of symptoms by affecting various organs. Here, we aimed to evaluate the prevalence, causes, and prognosis of sensorineural hearing loss (SNHL) occurring in children with Kawasaki disease.MethodsPatients who were diagnosed with Kawasaki disease and received inpatient treatment in the Pediatrics Department at one of three university hospitals in Daegu city from February 2012 to September 2012 were enrolled in the study. The clinical features, hematological results, echocardiography results, audiometry results, and aspirin and salicylic acid serum levels of the patients were evaluated.ResultsOf the 59 children enrolled in the study, three showed mild bilateral SNHL on audiometry tests conducted after 48 hours of defervescence; these patients demonstrated normal patterns of recovery on follow-up tests 8 weeks later. Aspirin serum levels were significantly higher in the SNHL group after 48 hours of afebrile condition with high dose aspirin intake (P=0.034). However, no significant differences were found in other laboratory tests or for fever duration (P>0.05). Upon echocardiography, coronary artery abnormality was observed in 9 cases, but none of these patients showed hearing loss.ConclusionThe results indicate that SNHL in children with Kawasaki disease might occur during treatment of the acute phase; this SNHL usually involves mild bilateral hearing loss and recovers naturally. However, this study suggests that determination of the causes and clinical implications of hearing loss in Kawasaki disease requires long-term follow-up studies with more cases.